Changes in the expression of N- and O-glycopeptides in patients with colorectal cancer and hepatocellular carcinoma quantified by full-MS scan FT-ICR and multiple reaction monitoring - Darebna, Petra; Novak, Petr; Kucera, Radek; Topolcan, Ondrej; Sanda, Miloslav; Goldman, Radoslav; Pompach, Petr (Journal of proteomics, 2017)
UNLABELLED: Alternations in the glycosylation of proteins have been described in connection with several cancers, including hepatocellular carcinoma (HCC) and colorectal cancer. Analytical tools, which use combination of liquid chromatography and mass spectrometry, allow precise and sensitive description of these changes. In this study, we use MRM and FT-ICR operating in full-MS scan, to determine ratios of intensities of specific glycopeptides in HCC, colorectal cancer, and liver metastasis of colorectal cancer. Haptoglobin, hemopexin and complement factor H were detected after albumin depletion and the N-linked glycopeptides with fucosylated glycans were compared with their non-fucosylated forms. In addition, sialylated forms of an O-linked glycopeptide of hemopexin were quantified in the same samples. We observe significant increase in fucosylation of all three proteins and increase in bi-sialylated O-glycopeptide of hemopexin in HCC of hepatitis C viral (HCV) etiology by both LC-MS methods. The results of the MRM and full-MS scan FT-ICR analyses provide comparable quantitative readouts in spite of chromatographic, mass spectrometric and data analysis differences. Our results suggest that both workflows allow adequate relative quantification of glycopeptides and suggest that HCC of HCV etiology differs in glycosylation from colorectal cancer and liver metastasis of colorectal cancer. SIGNIFICANCE: The article compares N- and O-glycosylation of several serum proteins in different diseases by a fast and easy sample preparation procedure in combination with high resolution Fourier transform ion cyclotron resonance mass spectrometry. The results show successful glycopeptides relative quantification in a complex peptide mixture by the high resolution instrument and the detection of glycan differences between the different types of cancer diseases. The presented method is comparable to conventional targeted MRM approach but allows additional curation of the data.
Keywords: diferenciální diagnóza; kolorektální nádory; Glycopeptides; Glycomics; hepatitida C; FT-ICR; Hepatocellular carcinoma; Hepatitis C; hepatocelulární karcinom; cyklotrony; Hemopexin; Glycosylation; Haptoglobin; Colorectal Neoplasms; O-glycopeptides; lidé; nádory jater; Carcinoma, Hepatocellular; Mass spectrometry; N-glycopeptides; Fourier Analysis; Fourierova analýza; hmotnostní spektrometrie; Diagnosis, Differential; MRM; Liver Neoplasms; Quantification; glykosylace; Mass Spectrometry; glykopeptidy; Cyclotrons; Humans